Genetic Polymorphism of Cyp2a6 and Cyp2a13 Genes and Environmental Tobacco Smoke Induced Lung Cancer Risk in Indonesian Female Never Smokers - Soeroso, Noni; Zain-Hamid, Rozaimah; Bihar, Syamsul; Tarigan, Setia Putra; Ananda, Fannie Rizki (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The presence of nicotine metabolite in the urine of subjects exposed to tobacco smoke represents the nicotine metabolism activity in environmental tobacco smokers. CYP2A6 and CYP2A13 are known as the main enzymes responsible for nicotine metabolism and xenobiotic activity in tobacco smoke-related lung cancer. AIM: The aim of this study is to analyze the relationship between genetic polymorphism of CYP26 and CYP2A13 genes and environmental tobacco smoke-induced lung cancer risk in Indonesian females never smoker. METHODS: This is a case-control study with two-stage of distinguishing polymorphism detection. Restriction fragment length polymorphism polymerase chain reaction from venous blood extraction was performed to examine the CYP2A6 and CYP2A13 polymorphism. Logistic regression test in Epi Info-7 software was carried out to examine genetic polymorphism of CYP2A6 and CYP2A13 genes and environmental tobacco smoke-induced lung cancer risk in Indonesian female never smokers. RESULTS: A total of 203 participants enrolled in this study with the first stage of CYP2A6 polymorphism involved 101 subjects showed no significant correlation between the genotypes of CYP2A6 and the incidence of lung cancer. On the other hand, there was a significant correlation between genotypes of CYP2A13 and the incidence of lung cancer (p < 0.05). People with the genotype CT have a 2.7 higher risk for developing lung cancer compare with genotype CC. Allele *1B was the most common allele in CYP2A6. Allele C has more frequencies and has 0.62 times the risk for developing lung cancer compared with allele T with a wide range of confidence intervals (0.73–3.52). CONCLUSIONS: There was a significant correlation between polymorphism CYP213 with the incidence of lung cancer among female lung cancer never smoker. However, the results show no significant relationship between CYP2A6 genetic polymorphism and lung cancer incidence.